Η συμβολή της Εκπαιδευτικής Τηλεόρασης στην εξ αποστάσεως Σχολική Εκπαίδευση - Papadimitriou, Sofia Theodor (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2020)
The continuous progress of new technologies transforms rapidly the field of education and it offers the necessary functional and friendly infrastructure for the development of distance education in schools. SDE can support a wide range of learning needs and offer effective solutions to the problems of geomorphology, pandemics, lack of teachers, supplementary or differentiated teaching, etc. by supporting both teachers in their work and students to enhance their performances. Innovative and flexible forms of learning are encouraged in SDE such as individualized, collaborative, experiential and exploratory learning. The expansion of the autonomous and complementary SDE in the range of formal education is considered necessary in Greece in the context of supporting equal educational opportunities. Fragmentary initiatives had been launched in formal and non-formal education system or innovative actions in the SDE, till the outbreak of the COVID-19 pandemic in March 2020. Then SDE evolves rapidly in the form of "Emergency Remote Teaching". This form was temporarily activated in response to the crisis, with the positive response and participation of teachers without a wide range of options and full management control. The complex conditions that are being faced require new roles for all stakeholders in school education. Educational systems are tested on the ways / methods of maintaining the educational practice outside of school in matters of pedagogical responsibility and technological readiness. With the outbreak of COVID-19 pandemic and the forced closure of schools, a great project of Emergency Remote Teaching began in Greece with synchronous, asynchronous teaching methods and TV broadcasts. Educational RadioTelevision (EduTV) of the Ministry of Education today supports students and teachers, encouraging their participation in authentic learning environments, which can inspire and offer conditions for collaborative creativity and cultivation of 21st century skills. EduTV produces educational audiovisual content specially designed and developed based on the Distance Education principles, which can furthermore support interactive communication. In addition to production, EduTV contributes to SDE in the dimensions of mass broadcasting through public television, distribution in digital repositories with open licenses, enabling integration and interaction in online learning environments. The open source H5P software offers teachers a strongly powerful tool to create their own interactive videos as part of their educational plans and practices in classrooms, Web learning environments or combining them by inserting interactive elements. The paper first presents an introduction to Distance Education and its principles and then emphasizes in SDE and the concepts of autonomous and complementary SDE. The second section approaches the role of EduTV in SDE on the one hand in its traditional form with the production and dissemination of audiovisual material and on the other hand with the utilization of streaming media on the Internet. The third section focuses on the initiatives of the EduTV in both SDE and Emergency Remote Teaching. Moreover it highlights the potential of video-lessons accessible by students with hearing problems, produced during the pandemic. The paper highlights the conclusions from the contribution of EduTV in front of the challenges that arise from the convergence of television and Internet technologies as well as from the complex conditions of 21st century education. The contribution of EduTV to SDE is highlighted as well as the ways in which it can support traditional school education and propose solutions to the complex pandemic situations or the geomorphological situations of the Greek school and moreover the special educational needs of students.